Association of inflammation gene polymorphism with increased risk of metabolic syndrome in tatar ethnic group - Olga V. Kochetova; Diana S. Avzaletdinova; Gulnaz F. Korytina (Russian Open Medical Journal)
Background and objective — Chronic low-grade inflammation plays an important role in pathophysiology of metabolic syndrome (MetS). The aim of our study was to determine the associations of polymorphic variants of inflammation genes with MetS and serum levels of high-sensitivity C-reactive protein (hsCRP) and tumor necrosis factor-α (TNF-α) in Tatar patients (Bashkortostan). Methods — In our case-control cross-sectional study, 271 MetS patients and 327 healthy Tatars were genotyped for the SNPs in CRP, TNFA, LTA, TNFRSF1B genes. Results — TNFRSF1B (rs1061624) was associated with the MetS [odds ratio (OR)=0.49, рADJ=0.0034] and TNF-α level (p=0.033). TNFA (rs1800629) was associated with TNF-α (p=0.015), albuminuria (p=0.013). CRP (rs2794521) was associated with fasting (p=0.0096) and postprandial (p=0.01) insulin, HOMA-IR (homeostasis model assessment of insulin resistance, p=0.0019), hsCRP (p=0.036), waist-hip ratio (WHR, p=0.007), body mass index (BMI, p=0.039). The participants having the C-C haplotype of CRP rs2794521-rs1130864 were more common among MetS patients (OR=1.99, p=0.032). T-T haplotype in CRP was associated with hsCRP (p=0.0043), low-density lipoprotein cholesterol (p=0.025), HOMA-IR (p=0.00029), glycated hemoglobin (p=0.006), postprandial (p=0.0006) and fasting insulin (p=0.00031), WHR (p=0.00012), BMI (p=0.00024). Conclusions — The data confirms that the variants of inflammation genes CRP, TNFA, TNFRSF1B are associated with levels of TNF-α, hsCRP. Novel association of TNFRSF1B (rs1061624) with MetS had been identified.